2009
DOI: 10.1264/jsme2.me09111
|View full text |Cite
|
Sign up to set email alerts
|

Dry-Resistance of Salmonella enterica subsp. enterica Serovar Enteritidis is Regulated by Both SEp22, a Novel Pathogenicity-Related Factor of Salmonella, and Nutrients

Abstract: Environmental isolates of Salmonella enterica serover Enteritidis (S. Enteritidis) clones were grown to the logarithmic phase, washed and re-suspended in saline or Luria-Bertani (LB) medium, and then 10-µL aliquots of the suspensions were dried overnight at room temperature. The dried bacteria were mixed with 1 mL of ice-cold PBS, suspended and examined for colony-forming activity. All of the pathogenic clones with high levels of SEp22, identical to Salmonella Dps, maintained good viability if suspended in LB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…We found that all of them, except egg white, elevated Salmonella survival rates under dry conditions after they were added to the bacterial suspension in saline before the drying protocol (25). In the present study, lactoferrin and apolactoferrin did not elevate Salmonella dry-resistance in saline, rather they inhibited it when they were added to 20% LB medium in saline.…”
Section: Inhibitory Effects Of Lactoferrin and Apolactoferrin On The contrasting
confidence: 49%
See 4 more Smart Citations
“…We found that all of them, except egg white, elevated Salmonella survival rates under dry conditions after they were added to the bacterial suspension in saline before the drying protocol (25). In the present study, lactoferrin and apolactoferrin did not elevate Salmonella dry-resistance in saline, rather they inhibited it when they were added to 20% LB medium in saline.…”
Section: Inhibitory Effects Of Lactoferrin and Apolactoferrin On The contrasting
confidence: 49%
“…2, SECl#15-1, a pathogenic strain of environmental isolates of S. Enteritidis, survived in considerable numbers in the presence of LB at concentrations of more than 10%, but it did not survive in saline alone, showing nutrition-dependence in the acquisition of dry-resistance as suggested in a previous paper (25). Therefore, we used 20% LB in saline for suspending Salmonella before drying throughout this study.…”
Section: Establishment Of An Assay Methods For Salmonella Dryresistancementioning
confidence: 86%
See 3 more Smart Citations